Liquid crystals based polarized random laser device for biomedical imaging applications - Muhammad Fa'iz Bin Ja'afar (Nanyang Technological University, 2023)
Random lasers have garnered substantial attention owing to their distinct emission characteristics and potential applications, especially within the applications of sensing and artefact-free imaging. When doped with dye molecules, random lasers based on nematic liquid crystals (NLCs) yield directional, polarized, and bright laser emissions—attributes of paramount significance in imaging applications. The primary objective of this project was to generate highly polarized random laser emission based on dye-doped NLCs. This report adopts a structured framework, offering a literature review of the research context, methodologies, experimental findings, and their advantages in the domain of imaging. In this experiment, a planar cell containing NLCs mixture E7 doped with 0.3weight% of Pyrromethene 597(PM597) dye was used as the sample. In order to obtain random lasing, the sample was optically pumped using a frequency-doubled Nd:YAG laser emitting 5 ns laser pulses at 532 nm. The results show that the lasing threshold was observed as the pump energy increased. There was a super-linear increase in the intensity above the threshold and a narrower emission spectrum was observed. The results also indicate that the laser emission was highly polarized, and it was linearly polarized along the nematic director (vertical direction). The random lasing based on dye-doped NLCs thereby demonstrated that the emission was indeed directional, polarized, and bright. The results suggest that random lasing based on dye-doped NLCs could serve as a potential light source for applications in biomedical imaging.